IMPROVED NEGATIVE SELECTION BASED DECISION BASED MEDIAN FILTER FOR NOISE REMOVAL - Kaur, Sarmandeep; Bawa, Navneet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
For de-noising an image, various filtering techniques are used but they have contradiction between noise removal and Edge preservation in an image. This de-noising contradiction has no efficient solution and they have to formulate a trade-off between the two contradictory aspects. In this paper we purpose a new technique that remove the noise and also preserve edges from image. This paper has proposed a new approach which will use decision tree structure to replace the noisy pixel in given window. The proposed technique seems to be effective as it will replace the noisy pixel with its best suitable alternative which is evaluated using negative selection based algorithm. The comparative analysis has clearly shown that the proposed technique outperforms over the available techniques.